Linking oral microbiota to periodontitis and hypertension unveils that Filifactor alocis aggravates hypertension via infiltration of interferon-γ+ T cells - Jun Zhang; Bo-Yan Chen; Meng-Fan Zhi; Wen-Zhen Lin; Yu-Lin Li; Hui-Lin Ye; Shuo Xu; Hong Zhu; Lu-Jun Zhou; Lin-Juan Du; Xiao-Qian Meng; Yan Liu; et al. (mSystems)
ABSTRACT Periodontal disease (PD), an inflammatory disease initiated by oral microbiota, may aggravate hypertension (HTN). Few studies were employed to characterize the oral microbiota in hypertensive patients with periodontitis. To investigate the interplay between oral microbiota and hypertension in individuals with periodontitis, we initiated a metagenomic sequencing study on subgingival plaque and saliva samples sourced from HTN patients and those with hypertension and periodontitis (PDHTN). Our primary objective was to characterize species serving as pivotal links (bridge species) in exacerbating hypertension induced by periodontal disease. Within subgingival plaque and saliva specimens, we pinpointed 31 and 28 bridge species, respectively. Furthermore, we noted a decrease in the abundance of nitrate-reducing bacteria, such as Actinomyces spp., Rothia spp., and Veillonella spp., in PDHTN samples. Employing network analysis, we distinguished distinct polymicrobial clusters within the two patient groups. These bridge species coalesced into polymicrobial clusters, revealing intricate symbiotic and competitive relationships. To substantiate our findings, we leveraged an angiotensin II-infused animal model of ligature-induced periodontitis (LIP), confirming the contributory role of Filifactor alocis—a selectively analyzed subgingival bridge species—in exacerbating hypertension and upregulating the frequency of renal CD4+IFNγ+ and CD8+IFNγ+ T cells. Our study screened a list of species linking PD and HTN. PD may aggravate HTN by decreasing the abundance of nitrate-reducing bacteria and increasing the abundance of pathogens. Using an animal model, we demonstrated that F. alocis aggravates HTN via the accumulation of IFNγ+ T cells in the kidneys.IMPORTANCEBoth periodontal disease and hypertension are widely prevalent all over the world. PD may aggravate the development of HTN via oral microbiota. However, few studies were employed to characterize the oral microbiota in hypertensive patients with periodontitis. Here, the present study profiled the oral microbiota in hypertensive participants with periodontitis. We found that the depleted abundance of nitrate-reducing bacteria and the enriched abundance of pathogens. Finally, we validated the role of Filifactor alocis in exacerbating HTN via infiltration of IFNγ+ T cells in mice kidneys. Our study improved the understanding of oral microbiota linking PD and HTN.